Permeability and barrier layer properties of a woven carbon fibre polymer composite as battery packaging - K. Pattarakunnan; J. Galos; W. Tian; A.S. Best; I.L. Kyratzis; A .P. Mouritz (Composites Part C: Open Access, 2024)
Carbon fibre reinforced polymer (CFRP) laminates are used in various studies as Li-ion polymer (LiPo) battery packaging. However, their suitability as a packaging material is not well understood. The present study investigates the liquid absorption (water and lithium bis(trifluoromethanesulfonic)imide (LiTFSI) electrolyte immersion tests) and barrier layer properties (water vapour transmission rate (WVTR) and oxygen transmission rate (OTR) tests) of a 200 gsm woven CFRP laminate to assess its suitability as a battery packaging material. This is the first study to show that prolonged immersion in battery electrolyte does not change the mechanical properties of a woven CFRP laminate. Hence, the CFRP laminate may be suitable for structural battery components, such as current collectors and electrodes. However, CFRP should not be used as battery packaging, as OTR and WVTR values of the CFRP laminate were found to be five and one order of magnitudes higher than typical battery pouch materials (i.e. aluminium foil), respectively.